Pemeriksaan Rutin Swadaya Masyarakat bagi Kesehatan Lansia - Cahyo Setiadi Ramadhan; Siti Bahiroh (Universitas Muhammadiyah Yogyakarta, 2021)
The elderly group in Bantul Regency is about 8.4% of the total population. This number is quite significant and needs attention from the government because these elders are vulnerable. Physical weakness makes the elderly group experience vulnerability in terms of health. This situation was worsened by the low public awareness about health. The same condition also occurred in Sawahan Hamlet, Pendowoharjo, Sewon, Bantul. Accordingly, to overcome this condition, routine checks should be carried out. The government has provided adequate public health centers to maintain the health of the elderly in each sub-district. However, the patient load of each puskesmas and the distance to the puskesmas become undeniable obstacles, especially in the elderly group with decreased motor skills. For this reason, efforts were made to bring health checks closer to the community, especially the elderly, by encouraging people who have the ability to carry out routine health checks. The purpose of this community service program was to increase public awareness and knowledge, especially the elderly, of the importance of regular health checks. The methods applied in program implementation were tutorials as a medium of education and mentoring. The results showed that the elderly are more aware and willing to carry out regular and continuous examinations.